An Islamic reading of Thomas Gray’s “Elegy Written in a Country Churchyard” - Hasan, Md. Mahmudul (2018)
Perhaps, the earliest literary scholar to significantly discuss the issue of looking at English literature from an Islamic perspective is Syed Ali Ashraf (1925 – 1998). His “Islamic Principles and Methods in the Teaching of Literature” (1978) is a foundational work that discusses the place of literature in a total Islamic worldview. He talks about the fundamental moral responsibility of man on earth and looks at literature from that perspective. He argues that, being human production, literature as a whole cannot be completely good and completely bad, stating: “No human activity is entirely good or entirely bad because only God is absolutely good and Satan is absolutely bad” (1978: 52). Therefore, when approaching a text, practitioners of literary studies should bear in mind that some ideas it transmits can be acceptable in Islam, while some others cannot. Given this conceptual premise, this study will look at Thomas Gray’s “Elegy Written in a Country Churchyard” (1751) from Islamic perspectives and will seek to identify common grounds and differentiations between Islamic teachings and Gray’s ideas as expressed in the poem.